Persepsi dan Tantangan Pengguna terhadap Implementasi Core Tax Administration System (Coretax) di Indonesia - Raymond Tirta Kelana; Se Tin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The digital transformation of Indonesian tax administration entered a new phase in January 2025 with the launch of the Core Tax Administration System (Coretax), an integrated platform replacing legacy systems such as DJP Online, e-Faktur, and e-Bupot. However, initial implementation was characterized by technical disruptions, latent data synchronization, and the complexities of parallel operations. This exploratory qualitative study addresses the empirical gap regarding early user perceptions through interviews with 15 stakeholders in Bandung, including tax consultants and individual taxpayers, utilizing NVivo for data analysis. Findings indicate that while integrated reporting and billing offer significant functional benefits, user experiences are hindered by technical unreadiness and limited institutional support. Tax consultants appear to be the most sensitive to technical obstacles, whereas individual taxpayers focus on adapting to new digital workflows. To ensure a sustainable and user-friendly evolution, the study concludes that a user-oriented approach is essential, necessitating enhanced user experience (UX) design, strengthened support services, and transparent institutional communication. The digital transformation of Indonesian tax administration entered a new phase in January 2025 with the launch of the Core Tax Administration System (Coretax), an integrated platform replacing legacy systems such as DJP Online, e-Faktur, and e-Bupot. However, initial implementation was characterized by technical disruptions, latent data synchronization, and the complexities of parallel operations. This exploratory qualitative study addresses the empirical gap regarding early user perceptions through interviews with 15 stakeholders in Bandung, including tax consultants and individual taxpayers, utilizing NVivo for data analysis. Findings indicate that while integrated reporting and billing offer significant functional benefits, user experiences are hindered by technical unreadiness and limited institutional support. Tax consultants appear to be the most sensitive to technical obstacles, whereas individual taxpayers focus on adapting to new digital workflows. To ensure a sustainable and user-friendly evolution, the study concludes that a user-oriented approach is essential, necessitating enhanced user experience (UX) design, strengthened support services, and transparent institutional communication.